(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Oxygen and carbon isotope data of several benthic and planktonic species of Foraminifera from a regressive sequence in northeastern Italy indicate a watermass change during the Late Eocene, In the middle of zone P 16 the Belluno Basin Was temporari/y cut off from the open ocean. This was probably provoked by 1) worldwide sea—level Iowering during the Late Eocene •and 2) tectonic activity in the relict Tethyan realm and the adjacent areas. The isolation apparently resulted in a temporary salinity increase in the relict basin. A pronounced oxygen isotope excursion at the base of P 16 could be explained by diagenetic changes. The formation of globular cement in the chambcr cavities of Foraminifera is due either to phreatic water infiltration promoted by the preceding shoaling of the sedimentary environment, or to a temporarily increased geothermal gradient resulting from the volcanic activity in the Colli Euganei. The genera and species of the superfamily Buliminacea are enriched in 16O relative to the taxa belonging to the superfamily Cassidulinacea. The δ18C of Nodosariacea are mostly intermediate. The oxygen isotope fractionation of benthic Foraminifera caused by biologica) processes (i.e. vital effect) seems to be somehow related to the wall structure (e.g. systematic classification).